Covenants in the Qurʾān: Reflections on Seven Elements of the Maqāṣid Framework - Rane, Halim (Journal of Contemporary Maqasid Studies, 2024)
Covenant (‘ahd and mīthāq) occupies a central place in the Qurʾān but has been understudied and underrepresented in discourses about Islam. This article contributes to redressing this lacuna by conducting a content analysis of the Qurʾān, specifically the terms ‘ahd and mīthāq that refer to the concept of covenant. It applies the Maqāṣid Methodology and Framework developed by Jasser Auda to examine the concepts, objectives, values, commands, universal laws, groups, and proofs associated with covenants in the Qurʾān. Reading the Qurʾān in light of covenants provides a new perspective on issues of human existence and coexistence, including interreligious relations, coexistence with non-Muslims, and conditions governing the legitimate use of armed force in Islam. The article highlights the centrality and significance of covenants in the Qurʾān and contends that the study of covenants in the Qurʾān and sunnah ought to be integrated into Islamic studies curricula.